INTERFERENSI BAHASA JAWA KE DALAM BAHASA INDONESIA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA DALAM PERKULIAHAN KEPROTOKOLAN - Pitoyo, Andri (Jurnal Pena Indonesia, 2017)
This study to describes the form of lexical interference of Javanese language into Indonesian language in the protocolly lectures, the form of morphological interference of Javanese language into Indonesian Language, and the syntactic of interference form Javanese language into Indonesian language. This research uses qualitative descriptive research method, with contextual linguistic research strategy, that is language research with structural analysis on speech of language user society. Sources of data in this study as the form of a speech the students of Educational language and Indonesian literature programs FKIP Kediri who studied in the protocolly lectures for odd semester 2016. This study to analyze the findings of Javanese language interference in oral speeches of participants in the subjects of protocolly lectures in Educational language and Indonesian literature programs. The instrument of this research is self-researcher because the research is in the form of oral discourse. The techniques of data collection are using the technique of recording note and recording. While the data analyze was used the interactive model including reduction data, presentation data, and conclusion. The results of this study indicate that of the three types of lexical interference is the most when compared with morphological interference and syntax interference.  It can be seen from the number of lexical interference data found in student speech transcripts. Syntactic interference ranks for the second, then the third order of morphological interference.